Polanyi in Brussels: Supranational Institutions and the Transnational Embedding of Markets - Caporaso, James A.; Tarrow, Sidney (International Organization, 2009)
AbstractMany have argued that the success of European integration is predicated on reinforcing market structures and some have gone further to state that the creation of a transnational market results in a decoupling of markets from their national political and social frameworks, thus threatening to unravel historical social bargains. Drawing on the work of Karl Polanyi and John Ruggie and using their insights regarding the social embedding of markets, we dissent from this view by examining how the European Court of Justice (ECJ) has handled a key sector of the emerging European market—labor mobility. We argue that rather than disembedding markets, decisions of the ECJ—just as Polanyi and Ruggie would have predicted—activate new social and political arrangements. We find evidence for the development of a new legal and political structure, largely inspired by the Court but also imbricated in European Union legislation, at the regional level.
Keywords: European Court of Justice; embedded markets

Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
Keywords: biography; essence of fascism

Subaltern strategies and autonomous community building: a critical analysis of the network organization of sustainable agriculture initiatives in Andhra Pradesh - Kumbamu, Ashok (Community Development Journal, 2009)
This paper examines and analyses the organization and functioning of subaltern peasant sanghams (grassroot associations of the poor) and their place-based as well as network-based strategies in building autonomous local communities that challenge the consequences of neoliberal globalization in general and the commodification of agriculture and food in particular. The major objective of the counter-hegemonic organizational strategies is to build self-protective and subsistence communities, to mend the metabolic rift between nature and society, and to re-reconstruct social fabric within communities. The question remains is whether place-based autonomous communities can sustain in an increasingly globalizing world. To better understand these political dynamics, I use Karl Polanyi's concept of ‘double movement’ and examine the making of a double movement in Indian agriculture and its socio-political and ecological implications for the Indian peasantry. I use the organizational strategies and activities of the Deccan Development Society, a prominent non-governmental organization that has been working in Medak district for more than two decades, as an illustrative case study.
Keywords: community development; community organizing; double movement; metabolic rift; peasant studies

The Extended Case Method: Four Countries, Four Decades, Four Great Transformations, and One Theoretical Tradition - Burawoy, Michael (University of California Press, 2009)
In this remarkable collection of essays, Michael Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the twentieth century—the rise and fall of the Soviet Union and its satellites, the reconstruction of U.S. capitalism, and the African transition to post-colonialism in Zambia. Burawoy's odyssey began in 1968 in the Zambian copper mines and proceeded to Chicago's South Side, where he worked as a machine operator and enjoyed a unique perspective on the stability of advanced capitalism. In the 1980s, this perspective was deepened by contrast with his work in diverse Hungarian factories. Surprised by the collapse of socialism in Hungary in 1989, he journeyed in 1991 to the Soviet Union, which by the end of the year had unexpectedly dissolved. He then spent the next decade studying how the working class survived the catastrophic collapse of the Soviet economy. These essays, presented with a perspective that has benefited from time and rich experience, offer ethnographers a theory and a method for developing novel understandings of epochal change.
Keywords: social science; sociology

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Keywords: appropriation; destructive mode of coordination; social integration

Karl Polanyi in Budapest: On his Political and Intellectual Formation - Dale, Gareth (European Journal of Sociology / Archives Européennes de Sociologie, 2009)
AbstractA major thinker and inspiring teacher, Karl Polanyi's contributions have long been influential in a variety of disciplines, notably economic sociology and economic history. Two of his innovations, substantivist economic anthropology and the “double movement thesis,” are recognized as seminal. All of the works for which he is known, however, were written late in life, when in exile, and very little is known of his Hungarian writings, virtually none of which had, until now, been translated. Despite his fame, the biographical literature on Polanyi remains modest: some studies provide invaluable insights, yet all are brief. This article attempts to make some headway in remedying these lacunae. It sketches the contours of that extraordinary historical-geographical conjuncture in which he was formed, and explores his intellectual and political engagements in the Galilei Circle and the Radical Bourgeois Party. It seeks in particular to elucidate the complex roles played by questions of nation, ethnicity and class in the life of the young Karl Polanyi.
Keywords: Hungary; Jewish assimilation; biography; liberal radicalism

Precarious Work, Insecure Workers: Employment Relations in Transition - Kalleberg, Arne L. (American Sociological Review, 2009)
The growth of precarious work since the 1970s has emerged as a core contemporary concern within politics, in the media, and among researchers. Uncertain and unpredictable work contrasts with the relative security that characterized the three decades following World War II. Precarious work constitutes a global challenge that has a wide range of consequences cutting across many areas of concern to sociologists. Hence, it is increasingly important to understand the new workplace arrangements that generate precarious work and worker insecurity. A focus on employment relations forms the foundation of theories of the institutions and structures that generate precarious work and the cultural and individual factors that influence people's responses to uncertainty. Sociologists are well-positioned to explain, offer insight, and provide input into public policy about such changes and the state of contemporary employment relations.
Keywords: precarious work; precarity

Embeddedness of Social and Economic Relations in Systemic Transformation. Long-Term Evidence From the Post-Communist Transition in Poland, 1988-2003 - Wilk, Katarzyna (Polish Sociological Review, 2009)
This paper intervenes in the Granovetter-Polanyi debate by reassessing the level of embeddedness of social and economic relations under conditions of systemic transition. Using panel data collected in Poland, this analysis examines this relationship for three distinct periods of transition: initial (1988-1993), advanced (1993-1998), and post-transitional (1998-2003). This paper shows that during transition from communism to capitalism economic relations tended to disembed from social relations, but this relationship remained significant; friendship ties were conductive to an individual upward mobility, economic well-being and entrepreneurial activity. In contrast to Polanyi's argument, however, entrepreneurship—the most marketable area of individual advancement—is found to exhibit the highest degree of social-economic embeddedness. These results do not directly support either Polanyi's or Granovetter's arguments, however they do accord with a neo-Polanyian argument, as advanced in this paper.
Keywords: (dis)embeddedness; Poland; capitalism; disembeddedness; embeddedness; entrepreneurship; friendship ties; political doctrines; practical politics; social classes; social networks; social status; socioeconomics; status attainment

Who is right about the modern economy: Polanyi, Zelizer, or both? - Steiner, Philippe (Theory and Society, 2009)
Zelizer’s work may be read as an attack on the central Polanyian thesis: that the market system threatens social life by the undue prominence it lends the economy in the organization of modern society. The recent publication of Viviana Zelizer’s The Purchase of Intimacy (2005a) is therefore an excellent opportunity to review the general trend of her work Zelizer 1979, 1985, 1994, and contrast her leading ideas to the central thesis that gives Polanyi’s work its particular flavor: the danger encapsulated in the use of modern money and the functioning of the market system.
Keywords: ZELIZER, Viviana; market system; money

Una lectura transversal de la Formación Profesional Ocupacional pública: entre Karl Polanyi, Max Weber y Michel Foucault - Dautrey, Philippe (Cuadernos de Trabajo Social (Espana) Vol. 22, 2009)
La formación profesional ocupacional (FPO) se ubica en una encrucijada de problemáticas que analizaron tanto Karl Polanyi como Max Weber y Michel Foucault. Por un lado, el papel fundamental que desempeñan los mercados autorregulados en el nuevo gran cambio que significa la globalización suscita un movimiento contraprotector del que participa esta capacitación para el empleo. Por otro, respalda el desarrollo de la organización racional capitalista, la cual a su vez implica su racionalización. Por último, es parte del control social que tal organización necesita para llevar a cabo sus propósitos. En resumen, las todavía relevantes obras de dichos estudiosos ofrecen una perspectiva diacrónica sobre el entorno de la FPO. También permiten apreciar el papel equívoco que ésta cumple respecto al desenvolvimiento y a los valores del sistema socio-económico vigente. ENG: The occupational vocational training (FPO) is located at a crossroads of problems that analyzed both Karl Polanyisuch as Max Weber and Michel Foucault. On the one hand, the fundamental role played by self-regulated markets in the new great change that globalization means provokes a counterprotective movement in which this training for employment is involved. On the other, it supports the development of rational capitalist organization, which in turn implies its rationalization. Finally, it is part of the social control that such organization needs to carry out its purposes. In summary, the still relevant works of these scholars offer a diachronic perspective on the environment of the FPO. They also allow us to appreciate the equivocal role it plays in respect to the development and values ​​of the current socio-economic system.
Keywords: FOUCAULT, Michel, 1926-1984; Post-Fordism; Spain; WEBER, Max, 1864-1920; capitalism; capitalismo; control social; employment; formacion profesional; knowledge economy; racionalizacion de la economia; rationalization of the economy; social control; vocational training; work

Backwash and Beyond: the Assumption of "Social Man" vs "Economic man": From Karl Polanyi to Mark Granovetter——The Latest Developments of the New Economic Sociology - Deshun, Zang (The Journal of Gansu Administration Institute, 2009)
As the hard core of western economic theory, the "economic man" assumption has been contradicted and challenged by the "social man" assumption since it formatted, which promotes economic theory to have adjusted its protective belt to promote the development of economics discipline. Polanyi's " embedded" theory, as the base of economic sociology which takes "social man" assumption as its hard core, is a subversive critique to "economic man" assumption. Based on "social man", New Economic Sociology (NES), established by Granovetter and others, regards men as "social men" firstly, and examines their social relations and institutions, and then analyzes the incentive mechanism of economic behavior. NES supplementally and even alternatively explains some theories proposed by economic models driven by traditional rational choice and utility. Thus, communion and dialogue has become inescapable to those subjects which are the same studying objects of the two disciplines.
Keywords: economic man; embeddedness

Polanyi, lecteur de Marx - Maucourant, Jérôme (2009)
En premier lieu, c'est la critique du capitalisme et du fascisme comme la prolongation toujours possible de celui-ci qui nous semble devoir être traitée. L'interprétation chrétienne du marxisme, à laquelle se livre Polanyi, est une façon de comprendre la condition d'étrangeté qu'éprouve l'homme moderne face à lui-même ; cette interprétation permet aussi de voir dans le fascisme la négation même du socle judéo-chrétien qui fonde en Occident la communauté humaine authentique. En second lieu, nous aborderons la question du contenu et de la construction du socialisme. Si, pour Polanyi, le socialisme est la réponse chrétienne aux défis posés par l'âge industriel, en revanche, la démocratie n'est pas une simple "superstructure" du capitalisme : une ambiguïté de l'œuvre de Marx est alors soulignée. Le socialisme, selon Polanyi, est l'extension du constitutionnalisme à la sphère de l'économie. Aux mirages de l'économie de commandement, Polanyi, dès 1922, oppose déjà la nécessité éthique d'une économie décentralisée impliquant la responsabilité des producteurs-associés. D'ailleurs, la signification du socialisme semble liée à la façon politique de l'instituer. Polanyi est hostile à la doctrine selon laquelle la stricte préservation de l'intérêt économique d'une classe sociale est à même d'assurer sa sauvegarde à long terme, car la lutte de classes doit tenir compte d'enjeux sociaux globaux. D'une façon générale, contre toute forme de déterminisme, singulièrement celui de la IIième internationale, Polanyi oppose la valeur de ce qui est dû aux choix conscients et responsables. Enfin, nous présenterons les débats anthropologiques qui marquèrent la seconde grande période de l'itinéraire de Polanyi. Jusqu'en 1936, il est possible d'inclure Polanyi dans le courant austro-marxiste ; après 1950, Polanyi critique l'idéologie économique qui caractérise nombre d'aspects du travail des sciences sociales. Les figures du travail de Marx qui sont inspirées par l'économisme occidental sont dénoncées par Polanyi ; mais Polanyi lui-même et certains membres de son école distinguent bien Marx d'Engels. Il n'en reste pas moins que les investigations de Polanyi sont une façon de conserver certains acquis du travail de Marx tout en s'émancipant du cadre de la dialectique. Popper lui-même reconnaît une dette envers Polanyi : celui-ci lui aurait montré les vertus d'un "nominalisme méthodologique" pour les sciences sociales dans les années 20. C'est cette même attitude qui inspire le programme Columbia des années 50 et qui provoque le rejet par certains marxistes de la méthode dite "substantive". Mais, ce que rejette Polanyi, ce n'est pas l'intérêt de l'analyse marxiste pour le capitalisme de son époque, c'est plutôt l'extension aux sociétés non-modernes de concepts imprégnés par la modernité ; c'est enfin, le refus de toute "loi" de développement social. Par où Polanyi, sans être cette façon d'anti-Marx à l'usage de "radicaux" pour les temps post-modernes, se révèle aussi pertinent qu'actuel. First, this is the critique of capitalism and fascism as the always possible extension of it seems we have to be treated. The Christian interpretation of Marxism by Polanyi is a way of understanding the condition of strangeness experienced by modern man in front of himself; This interpretation also makes it possible to see in fascism the very negation of the Jewish-Christian base which founds the authentic human community in the West. Second, we will address the question of the content and construction of socialism. If, for Polanyi, socialism is the Christian response to the challenges posed by the industrial age, democracy, on the other hand, is not a simple "superstructure" of capitalism: an ambiguity of Marx's work is underlined. Socialism, according to Polanyi, is the extension of constitutionalism to the sphere of the economy. To the mirages of the economy of command, Polanyi, already in 1922, already opposes the ethical necessity of a decentralized economy involving the responsibility of the associate producers. Moreover, the meaning of socialism seems to be linked to the political way of instituting it. Polanyi is hostile to the doctrine that the strict preservation of the economic interest of a social class is capable of ensuring its long-term safeguard, since the class struggle must take account of global social issues. In a general way, against all forms of determinism, particularly that of the Second International, Polanyi opposes the value of what is due to conscious and responsible choices. Finally, we will present the anthropological debates that marked the second major period of Polanyi's itinerary. Until 1936, it was possible to include Polanyi in the Austro-Marxist current; After 1950, Polanyi criticized the economic ideology that characterizes many aspects of social science work. The figures of Marx's work which are inspired by Western economism are denounced by Polanyi; But Polanyi himself and some members of his school distinguished Marx from Engels. The fact remains that Polanyi's investigations are a way of preserving certain of the achievements of Marx's work, while emancipating himself from the framework of the dialectic. Popper himself acknowledged a debt owed to Polanyi, who would have shown him the virtues of a "methodological nominalism" for the social sciences in the 1920s. It was this attitude that inspired the Columbia program of the 1950s, Provokes the rejection by certain Marxists of the so-called "substantive" method. But what Polanyi rejects is not the interest of Marxist analysis for the capitalism of his time, but rather the extension to modern societies of concepts imbued with modernity; Finally, the refusal of any "law" of social development. By which Polanyi, without being this way of anti-Marx to the use of "radicals" for the post-modern times, is as relevant as it is actual. Working paper or preprint
Keywords: MARX, Karl, 1818-1883; communism; communisme; fascism; fascisme; matérialisme historique; socialism; totalitarisme; vitalisme

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Keywords: double movement; economic sociology; neoliberalism

Human Rights and Business Practices: Double Movement or Neoliberal Hegemony? - Thomas, Mark (Conference Papers -- American Sociological Association, 2009)
Throughout the 1990s and into the early years of the 21st century, campaigns by labor rights activists brought the issue of labor exploitation by Northern transnationals (TNCs) operating in the Global South into the centre of public debate. Labor rights scholars raised the possibility of a broader Polanyian 'double movement' in the global economy, as the polarizing effects of neoliberal globalization produced anti-globalization movements and shifts towards forms of social protection through emerging approaches to transnational labor rights regulation. One of the results of these processes was the adoption of a human rights discourse by TNCs as they sought to re-define their public image in response to growing public awareness and condemnation of sweatshop labor practices. Read through a Polanyian lens, these developments would seem to confirm that a double movement was in fact producing a more socially responsible capitalism where the 'satanic mill' of the sweatshop would be moderated through corporations proclaiming respect for human rights. In this paper, I examine the adoption of human rights principles by corporate actors as both normative framework and business practice. I argue that rather than a double movement from market liberalism to social protection, the dynamics present in this process indicate tendencies towards the construction of a new hegemonic discourse to support neoliberal globalization - that of the 'socially responsible' corporation where business practices and human rights principles intersect. ..PAT.-Unpublished Manuscript
Keywords: employee rights; hegemony; human rights; neoliberalism; satanic mill; transnationalism

Markets Against Society: Labor's Predicament in the Second Great Transformation - Webster, Edward; Lambert, Robert (The ISA Handbook in Contemporary Sociology: Conflict, Competition, Cooperation, 2009)
Keywords: labour movement; northern compromise; second great transformation